Prosedur Pelayanan dan Sistem Pembayaran Pajak Kendaraan Bermotor UPTD Pengelolaan Pendapatan Daerah Sibolga Badan Pendapatan Daerah Provinsi Sumatera Utara - Lubis, Nabila; Sudiarti, Sri (Jurnal Penelitian Multidisiplin Ilmu, 2024)
One of the most promising sources of local revenue (PAD) is motor vehicle tax (PKB). Because it has the ability to increase Regional Original Revenue (PAD) in each region, the UPTD PEPENDA of the Sibolga Regional Revenue Agency plays an important role in organizing local government in this regard. Therefore, the local government sees a huge opportunity to make all motorized vehicles owned by taxpayers the subject of Motor Vehicle Tax (PKB). This is related to the growth and development of the budget function which requires local governments to always look for new sources of funding. As well as sources that are owned and considered to have the ability to bring in money for the region. Taxpayers who own motorized vehicles are required to pay Motor Vehicle Tax (PKB). A taxpayer is considered compliant with the applicable laws and regulations if he has paid his Motor Vehicle Tax. In accordance with Law No. 28/2009, taxpayers who do not make payments on time may be subject to fines or administrative sanctions. Based on the internship activities that have been carried out by researchers at the One-Stop Manunggal Administration System (SAMSAT) Office, it appears that there are indications of a lack of discipline in carrying out several tasks. There is still a lack of discipline towards time estimation with employees who are not on time during work hours.